Luxembourg : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Selected Issues Paper analyzes the fiscal position and significant challenges for Luxembourg. Luxembourg's fiscal position is currently sound, however, fiscal safety buffers are being eroded. The country's healthy fiscal position will be challenged by forthcoming revenue losses as well as rapid trend growth in expenditures. An overall strategy to address this coming deterioration is needed. Beyond the planned value-added tax increase, recurrent property taxes are a possible additional source of revenue. On expenditures, social benefits should be an area of focus, and reforms of these benefits should also aim to reduce disincentives to work.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet